Implications of population size, structure, and soil parameters for the conservation of Allochrusa gypsophiloides in Kazakhstan - ASEM TASTANBEKOVA; KANAT KULYMBET; MERUYERT KURMANBAYEVA; MARIA HÖHN; MOLDIR ZHUMAGUL; OZODBEK ABDURAIMOV; GANI I. ISSAYEV; ORYNBASSAR ALSHYNBAYEV; MURAT TOKTAR; ZHASSULAN SMANOV (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Tastanbekova A, Kulymbet K, Kurmanbayeva M, Höhn M, Zhumagul M, Abduraimov O, Issayev GI, Alshynbayev O, Toktar M, Smanov Z. 2025. Implications of population size, structure, and soil parameters for the conservation of Allochrusa gypsophiloides in Kazakhstan. Biodiversitas 26: 2051-2064. The study examines the distribution, population size, and ecological conditions of Allochrusa gypsophiloides in the Karatau Mountain Range, Kazakhstan. This rare species, listed in the Red Data Book, was found in four populations (P1-P4): Sayasu Gorge (P1), Kuyuk Pass (P2), and The Vicinity of Birlik (P3) and Kenestobe Villages (P4). Geobotanical research assessed species composition, plant communities, and ontogenetic structure using Uranov’s classification. Soil properties, including humus content, nutrient levels, and pH, were analyzed. The total number of A. gypsophiloides individuals across all sites was 91, with low population densities (0.15-0.29 individuals/m²). Age structure analysis revealed no senile individuals, with generative individuals predominating in two populations. Generative (g1) individuals accounted for 20.0% in P1 and 18.52%, 24.14%, and 33.34% in P2-P4, respectively. Post-generative (sub-senile) individuals were rare (0-13.34%). Despite a relatively stable age composition, low population density remains a concern. Soils across populations shared similar characteristics: low humus and nutrient content, moderately to strongly alkaline pH, and sandy loam to medium loam textures. The species' restricted distribution, low density, and specific soil requirements make it highly vulnerable to environmental changes and human activities. Conservation efforts of A. gypsophiloides should be aimed at protecting key habitats (Sayasu Gorge, Kuyuk Pass, and The Vicinity of Birlik and Kenestobe) with limited economic activity, introducing a system for long-term monitoring of the number and age structure of populations using standardized techniques, as well as assessing opportunities for reintroduction of the species to suitable sites. Further research on reproductive biology and ecological interactions is essential for ensuring the species' long-term survival in the Syrdarya Karatau Mountain Range.